Descriptive analyses and risk of death due to Ebola Virus Disease, West Africa, 2014 - Folorunso Oludayo Fasina; Olubukola T. Adenubi; Samuel T. Ogundare; Aminu Shittu; Dauda G. Bwala; Modupe M. Fasina (Journal of Infection in Developing Countries, 2015)
Introduction: Since the first case of Ebola virus disease (EVD) in Guinea in 2013, major outbreaks have been reported in West Africa. Methodology: Cases and fatalities of EVD caused by Zaire Ebola virus (ZEBOV) were evaluated, and the risks of dying in the general population and in healthcare workers were assessed. Results: The case fatality rate estimated for EVD was 76.4% in 20 studies. Cumulative proportion of fatal cases in West Africa was 42.9%, 30.1%, and 64.2% in Liberia, Sierra Leone, and Guinea, respectively. The proportion of total deaths in Liberia, Sierra Leone, and Guinea was 42.5%, 35.8%, and 21.6%, respectively. Healthcare workers were at higher risk of dying compared with the general public, and the same applied to intense transmission countries and to countries with sufficient bed capacities. The declaration of a health emergency “out-of-control” situation by the World Health Organization on 8 August 2014 reduced the risk of death among patients. Factors including deplorable healthcare delivery infrastructure in war-ravaged regions of Africa, the impotence of governments to enforce public health regulations, and the loss of confidence in public healthcare delivery programs were key among others factors that enhanced the spread and magnitude of outbreaks. Conclusions: The findings underscore the need for an overall re-appraisal of the healthcare systems in African countries and the ability to cope with widespread epidemic challenges. Outbreaks like that of Ebola diseases should be handled not just as a medical emergency but also a socio-economic problem with significant negative economic impacts.